An Overview Of Golden Spice's (Turmeric) Medicinal Properties For Future Development Potential - Zarini Ismail; Nur Ain Nabila Mazuki (Universiti Sains Islam Malaysia, 2024)
MJoSHT 2020, Volume 6, Special Issue, eISSN: 2601-0003